Pengaruh Biaya Promosi Terhadap Penjualan Produk Pada PT Asuransi Asei Indonesia - Syafira, Nicky Inca; Sari, Meigia Nidya (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2024)
This research aims to analyze the effect of promotional costs on increasing product sales at PT. Asei Indonesia Insurance. The research was carried out in October 2023. Library research method for data collection. The analysis method uses Descriptive analysis, Simple Regression Test and T Test. The results of SPSS data processing regarding promotional costs and sales volume show that promotional costs (X1) have a calculated t value of 3,153 > from t table 1.65291. Judging from the sig t value (0.034) < 0.05. As a result, Ha is accepted and H0 is rejected, testing the research hypothesis. This shows how promotional costs affect product sales at PT. Asei Indonesia Insurance. The results of the coefficient of determination test provide meaning, that 71.3% is influenced by the promotional cost variable while 8.7% is influenced by other variables outside this research based on interval criteria where the coefficient of determination results is at a value of 0.60 - 0.799, which means it has a strong relationship. strong relationship between promotional costs and sales